PERSEPSI STAKEHOLDER TERHADAP KETERBUKAAN INFORMASI DALAM MEMBANGUN TATA KELOLA PEMERINTAHAN YANG BAIK DI KOTA KENDARI - Andi Syaiful Zainal; Riston G. Ahmad; Dian Arwulan; Musridwan; Mulyawan (Journal Publicuho, 2023)
This research focuses on stakeholder perceptions of information transparency, the aim is to contribute to the development of effective governance. The main problem is the low transparency of information which hinders the development of participatory governance in Kendari. This study aims to analyze stakeholder perceptions, formulate strategies to increase transparency, and measure the impact of implementing these strategies. The literature review involves the concepts of governance, information transparency, and stakeholder perceptions. Variables include information access, trust, and stakeholder participation. Qualitative methods with interviews, observations and FGDs are used, supported by the analysis of official documents. This research fills in a gaping body of literature on stakeholder perceptions at the local level, providing insight into the dynamics of local information transparency. Data analysis uncovered positive impacts, including improved accountability, participation, and decision quality. Challenges involve budget constraints and community understanding. Recommendations involve increased community understanding, evaluation of administrative barriers, and adequate budget allocation. These conclusions provide a clear picture, highlight challenges, and offer direction for future improvements regarding information transparency and governance in Kendari.